Challenges and Priorities for Pediatric Critical Care Clinician-Researchers in Low- and Middle-Income Countries - von Saint André-von Arnim, Amelie O.; Attebery, Jonah; Kortz, Teresa Bleakly; Kissoon, Niranjan; Molyneux, Elizabeth M.; Musa, Ndidiamaka L.; Nielsen, Katie R.; Fink, Ericka L.; , The Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) Network (Frontiers in Pediatrics, 2017)
Introduction There is need for more data on critical care outcomes and interventions from low- and middle-income countries (LMIC). Global research collaborations could help improve health-care delivery for critically ill children in LMIC where child mortality rates remain high. Materials and methods To inform the role of collaborative research in health-care delivery for critically ill children in LMIC, an anonymous online survey of pediatric critical care (PCC) physicians from LMIC was conducted to assess priorities, major challenges, and potential solutions to PCC research. A convenience sample of 56 clinician-researchers taking care of critically ill children in LMIC was targeted. In addition, the survey was made available on a Latin American PCC website. Descriptive statistics were used for data analysis. Results The majority of the 47 survey respondents worked at urban, public teaching hospitals in LMIC. Respondents stated their primary PCC research motivations were to improve clinical care and establish guidelines to standardize care. Top challenges to conducting research were lack of funding, high clinical workload, and limited research support staff. Respondent-proposed solutions to these challenges included increasing research funding options for LMIC, better access to mentors from high-income countries, research training and networks, and higher quality medical record documentation. Conclusion LMIC clinician-researchers must be better empowered and resourced to lead and influence the local and global health research agenda for critically ill children. Increased funding options, access to training and mentorship in research methodology, and improved data collection systems for LMIC PCC researchers were recognized as key needs for success.